2006
DOI: 10.1309/qc259f09unmkvp0r
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Factor XI Activity Levels Are Associated With an Increased Odds Ratio for Cerebrovascular Events

Abstract: High levels of factor XI have been implicated as a risk factor for deep venous thrombosis and possibly cardiovascular disease; however, the relationship between elevated factor XI activity and stroke has yet to be established. We retrospectively evaluated factor XI activity, factor XI antigen, and high-sensitivity C-reactive protein (hs-CRP) values in samples from 65 patients with stroke, 13 with transient ischemic attack (TIA), and 17 with venous thrombosis, younger than 55 years with normal prothrombin and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(63 citation statements)
references
References 18 publications
2
54
1
1
Order By: Relevance
“…Patients with severe FXI deficiency were reported to exhibit protection from ischemic stroke and a lower incidence of venous thromboembolism (VTE) [24,25]. Conversely, higher levels of FXI were associated with increased risk of VTE and ischemic stroke [26,27]. Reducing factor XI levels in patients undergoing unilateral total knee arthroplasty has been shown to be an effective method for the prevention of postoperative VTE, suggesting FXI inhibition as an effective method of anticoagulation in surgery [28].…”
Section: Fxi and Thrombosismentioning
confidence: 99%
“…Patients with severe FXI deficiency were reported to exhibit protection from ischemic stroke and a lower incidence of venous thromboembolism (VTE) [24,25]. Conversely, higher levels of FXI were associated with increased risk of VTE and ischemic stroke [26,27]. Reducing factor XI levels in patients undergoing unilateral total knee arthroplasty has been shown to be an effective method for the prevention of postoperative VTE, suggesting FXI inhibition as an effective method of anticoagulation in surgery [28].…”
Section: Fxi and Thrombosismentioning
confidence: 99%
“…Notably, high levels of FXI are associated with increased risk of stroke and associated marginally with myocardial infarction. 19,20 However, in patients with severe FXI deficiency, a reduced incidence of ischemic stroke but not of myocardial infarction was observed. 21,22 In animal models, it was shown that deprivation of FXI did protect against injury-induced thrombosis 23,24 and that apoE knockout mice treated with FXI antisense oligonucleotides were protected from thrombosis on acutely ruptured atherosclerotic plaques.…”
mentioning
confidence: 99%
“…This is comparable to the risk in people with high-normal plasma fIX levels [15]. Subsequent work demonstrated that high plasma fXI levels are associated with increased incidences of myocardial infarction and ischemic stroke [16,17], whereas severe fXI deficiency lowers risk for ischemic stroke and venous thrombosis [18,19]. …”
Section: Rationale For Inhibiting Factor Xia To Treat or Prevent Thromentioning
confidence: 99%